Creative Crisis in Democracy and Economy - Bitros, George C.; Karayiannis, Anastasios D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Developments across the millennia suggest that, even though democracies and free market economies are continuously challenged by crises and disturbances, such as natural disasters, wars, or technological revolutions, in the countries where they take roots civil liberties deepen and per capita prosperity increases. To substantiate this claim analytically, the authors emphasize the principles that make free markets a sine qua non condition for democracy and study the nature of the relationship between free market institutions and economic growth. By examining the operating principles, outcomes and challenges experienced by contemporary democracies, many lessons are drawn with regard to how governments should act in order to avoid the pitfalls inherently associated with representative democracy. To illustrate the dangers of deviating from these principles, the authors apply their findings to the Greek democracy and economy since the Second World War.
The Athenian Democray -- The Classical Democracy -- The Contemporary Democracy -- A Digression on Social Democracy -- The New Classical Democracy -- The Place of Democracy in the World and Globalization -- Democracy, Free Market Economy and European Unification -- Democracy in the Future and the New Welfare State -- The Case of Contemporary Greece.
Keywords: Social sciences; Political science -- Philosophy; Finance; Social Sciences; Political Economy; Public Finance & Economics; Political Philosophy